Quantification of clearance and creep in acetabular wear measurements - Saffarini, Mo (Ann Transl Med, 2016)
BACKGROUND: This study aimed to measure femoral head penetration before occurrence of real wear, and to quantify the portions attributable respectively to clearance and plastic deformations in various acetabular designs. METHODS: We analyzed CT scans from 15 patients at ‘day five’ after total hip arthroplasty (THA). All patients received Exafit(®) femoral stems and 28 mm heads: 5 patients had cemented Durasul(®) all-PE cups, 5 patients had un-cemented Allofit(®) metal-backed cups, and 5 patients had un-cemented Stafit(®) dual-mobility cups. We also analyzed CT scans of samples of the three head-cup combinations to compare in vivo and in vitro measurements. RESULTS: The mean femoral head penetration measured on ‘day five’ was lower for all-PE cups (0.196 mm) than for metal-backed cups (0.551 mm) and dual-mobility cups (0.634 mm). CONCLUSIONS: The present study indicates that isolated measurements of femoral head penetration include 0.15–0.46 mm of radial clearance and 0.05–0.27 mm of creep, and confirms that the majority of so-called bedding-in observed in the first post-operative months is not entirely due to wear.